The state support of industrial and innovative activities in Kazakhstan: innovation grants - Mamrayeva, D.G. (Вестник Карагандинского университета, 2016)
In the article the goals, objectives and measures of the state support of industrial and innovative activity in the Republic of Kazakhstan at the present stage of economic development were disclosed. A number of legal documents regulating the innovation activity in the country was considered. Some of the elements of industrial-innovative infrastructure: special economic zones, industrial parks, technology commercialization centers, industrial design offices; international centers of technology transfer, innovation clusters were highlighted. The main types of innovation grants, issued by the State, in particular to support the production of high-tech products at the initial stage of development; conducting industrial research; patenting in foreign countries and (or) regional patent organizations; acquisition of technology; commercialization of technologies; introduction of managerial and production technologies were reflected.
Keywords: government support for industrial innovation; innovation grants; technological parks; industrial design offices; industrial and innovation infrastructure